The Meaning of Dabbah in Surah Ash-Shu'ara 29: An Astrobiological Approach - Erwanto, Dian; Azizah, Nur; Zuhroh, Naila Izzatuz; Maulidah, Dewi; Faidah, Faidah (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This research attempts to prove the truth of the Quran with scientific facts based on the meaning of